ENHANCING READING INSTRUCTION: EXPLORING EFFECTIVE STRATEGIES, ASSESSMENT TECHNIQUES, AND PROMOTING LITERACY DEVELOPMENT IN EDUCATION (Konferensiyalar | Conferences, 2024)
Reading proficiency is a foundational skill that underpins academic success across all subject areas. However, many students continue to struggle with reading, highlighting the need for effective and evidence-based reading instruction. This research article examines strategies to enhance reading instruction, including the implementation of targeted assessment techniques and the promotion of comprehensive literacy development in educational settings.